Initiation of knowledge and technology transfer from academia to industry: Opportunity recognition and transfer channel choice - Matthias Huegel; Philip Dörr; Martin Kalthaus (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
The transfer of knowledge and technology from academia to industry is usually understood as a process. While previous research focuses on phenomena along the process and its outcomes, the starting point of the process - the initiation of a transfer activity - remains unstudied. We provide first empirical insights on the initiation of the transfer process and conceptualize this initiation as a simultaneous recognition of a transfer opportunity and the choice of a transfer channel. We focus on Science-Industry collaboration, Intellectual Property Rights and spin-off creation as relevant channels. We use survey data from 1,149 scientists from the German state of Thuringia and utilize seemingly unrelated regressions to account for selection and multiple channel choices in our econometric approach. Our results show a positive relationship between scientists' probability to recognize a transfer opportunity and different kinds of prior knowledge. Contrary to our expectation, scientific quality reduces the likelihood of recognizing a transfer opportunity. For the choice of the transfer channel, the results show a positive relationship between choosing the spin-off channel and risk willingness, as well as basic research. Applied research increases the likelihood to choose Intellectual Property Rights as a channel. Furthermore, role models are positively associated with these two channels.
Keywords: L26; O31; O33; O34; 330; Transfer Process; Transfer Initiation; Opportunity Recognition; Transfer Channel; Science-Industry Collaboration; Intellectual Property Right; Academic Spin-off